Mechanisms underlying working memory in health and disease - Maio, MRH (2021)
Working memory (WM) — the means by which information is retained and manipulated over seconds — is a fundamental cognitive process that has been considered to have three phases: encoding, maintenance and retrieval. Although much research has focused on the first two of these, far less is understood about how information is retrieved from WM or how filtering of information in WM affects recall and forgetting, both in health and disease.